2021
DOI: 10.1021/acsami.1c03066
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared-Active Copper Molybdenum Sulfide Nanocubes for Phonon-Mediated Clearance of Alzheimer’s β-Amyloid Aggregates

Abstract: Ternary chalcogenide materials have attracted significant interest in recent years because of their unique physicochemical and optoelectronic properties without relying on precious metals, rare earth metals, or toxic elements. Copper molybdenum sulfide (Cu 2 MoS 4 , CMS) nanocube is a biocompatible ternary chalcogenide nanomaterial that exhibits near-infrared (NIR) photocatalytic activity based on its low band gap and electron−phonon coupling property. Here, we study the efficacy of CMS nanocubes for dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 69 publications
(139 reference statements)
0
25
0
Order By: Relevance
“…To examine the advent of the magnetoelectrically driven chemical reactions, we tested dihydroethidium (DHE) and terephtalic acid (TA) assays; DHE assay detects the occurrence of 2-hydroxyethidium through the electron transfer reactions and TA assay probes the generation of 2-hydroxyterephthalic acid based on the hole migration process (fig. S7) ( 28 , 35 ). We found that the excited charge carriers were transferred from the surface of BCFO nanoparticles to the reactants (i.e., DHE and TA) approximately 4.2 times more than that of CFO nanoparticles under a low-frequency magnetic field (1 kHz and 13.6 mT) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To examine the advent of the magnetoelectrically driven chemical reactions, we tested dihydroethidium (DHE) and terephtalic acid (TA) assays; DHE assay detects the occurrence of 2-hydroxyethidium through the electron transfer reactions and TA assay probes the generation of 2-hydroxyterephthalic acid based on the hole migration process (fig. S7) ( 28 , 35 ). We found that the excited charge carriers were transferred from the surface of BCFO nanoparticles to the reactants (i.e., DHE and TA) approximately 4.2 times more than that of CFO nanoparticles under a low-frequency magnetic field (1 kHz and 13.6 mT) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of Aβ fibril solution (40 μM) was carried out with a biocompatible Hepes buffer (pH 7.4) following previous studies ( 26 , 28 ). Morphologies of Aβ fibrils were recorded by an AFM instrument (NNOVA-LABRAM HR800, Horiba, Japan) (with an area of 5 μm by 5 μm and a line number of 512), SEM (S-4800, Hitachi, Japan) at 10 kV, and TEM (Talos F200X, FEI Company, USA) at 200 kV.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations